Implementasi Strategi Pemasaran Produk Menu Makanan Ikan Di Warung Bendega, Pantai Lebih, Gianyar dalam Meningkatkan Minat Beli Konsumen - Dewa Nyoman Sadguna; I Gusti Ngurah Sugiana; Ni Wayan Nia Apriliani (Fakultas Pertanian, Universitas Warmadewa, 2023)
Changes in people's consumption patterns and lifestyles have led to an increase in physical mobility driven by activities outside the home. This condition causes an increase in public demand for ready-to-eat food. The increasing demand for ready-to-eat food is an opportunity for entrepreneurs to start their own businesses. Thus every company must try hard to achieve its goals by using various ways, one of which is the development of an appropriate marketing strategy. The success of business development will affect the amount of profit received. The financial aspect is an important factor in a business. This research is descriptive qualitative which aims to determine the implementation of the marketing strategy used, the marketing mix implemented includes product, price, place and promotion and benefits of Warung Bendega, Lebih Beach, Gianyar. Income analysis in this study is calculated based on the difference between total revenue (TR) and total cost (TC). The results of the income analysis obtained in November 2022 amounted to Rp. 2.621.167. This shows that the income earned by Warung Bendega is relatively good so that Warung Bendega's business is feasible in terms of profits.